The age of digital opportunity : connecting the generations (UN ICT Task Force New YorkUS, 2003)
Presents insights on enhancing generational understanding. Looks at opportunities for ICT as a social and economic catalyst. Highlights special opportunities and challenges for older persons in the digital era. Looks at public-private partnerships, global perspectives and trends.
Keywords: ACCESS TO INFORMATION